2022
DOI: 10.1172/jci.insight.148960
|View full text |Cite
|
Sign up to set email alerts
|

Resident stroma-secreted chemokine CCL2 governs myeloid-derived suppressor cells in the tumor microenvironment

Abstract: Accumulating evidence has shown that cancer stroma and bone marrow-derived cells (BMDCs) in the tumor microenvironment (TME) play vital roles in tumor progression. However, the mechanism by which oral cancer stroma recruits any particular subset of BMDCs remains largely unknown. Here we sought to identify the subset of BMDCs that is recruited by cancer stroma. We established a sequential transplantation model in BALB/c nude mice, including (i) bone marrow transplantation of GFP-expressing cells and (ii) co-xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Recruitment and accumulation of Gr1 + CD11b + cells in the TME, particularly through the chemokines CCL2, CXCL1 and CXCL2, or IL-33, is considered a critical step for their contribution to tumor progression and metastasis (67)(68)(69)(70). Consistent with these observations, tumors derived from sorted 4T1-Sca-1 + cells, or MR13 cells that are intrinsically enriched for Sca-1 + cells, have a higher content of Gr1 high CD11b + Ly6C low cells compared to tumors derived from 4T1-Sca-1or parental 4T1 cells, respectively (Figure 2A and 5K).…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment and accumulation of Gr1 + CD11b + cells in the TME, particularly through the chemokines CCL2, CXCL1 and CXCL2, or IL-33, is considered a critical step for their contribution to tumor progression and metastasis (67)(68)(69)(70). Consistent with these observations, tumors derived from sorted 4T1-Sca-1 + cells, or MR13 cells that are intrinsically enriched for Sca-1 + cells, have a higher content of Gr1 high CD11b + Ly6C low cells compared to tumors derived from 4T1-Sca-1or parental 4T1 cells, respectively (Figure 2A and 5K).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously [ 7 ]. 5 μg protein mixed with 4× Laemmli sample buffer (Bio-Rad Laboratories, Hercules, CA, USA) was boiled at 95 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a higher proportion of stroma in OSCC relates to poor prognosis [ 4 , 5 ]. We also observed that incorporating different stromal cells into oral cancer xenograft models showed different effects on tumor progression, bone invasion, and bone marrow cell recruitment [ 6 , 7 ]. On the other hand, tumor angiogenesis supports tumor development, dissemination, and metastasis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many tumors secrete large amounts of CCL2, thereby recruiting circulating inflammatory monocytes into tumor tissues where they then differentiate into M2 TAMs ( 32 , 117 , 118 ). CCL2 may also play a minor role in PMN-MDSC recruitment, though the primary chemokine driving TAN recruitment is CXCL8 ( 119 ). There have been numerous preclinical studies in rodent models assessing inhibitors of the CCL2-CCR2 axis using either small molecule CCL2 inhibitors or monoclonal antibodies, and most have demonstrated inhibition of tumor growth and/or decreased metastatic burden ( 120 ).…”
Section: Therapeutic Targeting Of Immune Suppressive Macrophages and ...mentioning
confidence: 99%